Analisis Pencatatan Keuangan Desa Wisata sebagai Entitas Pelaporan Akuntansi pada Desa Wisata Karangrejo Borobudur - Tesa Br Simbolon; Putri Nur Setyowati; Desta Amanda Desfillia Azzahra; Suci Nasehati Sunaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the financial recording system, tourism revenue management, and the feasibility of Karangrejo Tourism Village as a public sector accounting reporting entity. The research employed a descriptive qualitative approach with field study methods. Data were collected through interviews, observation, and documentation, then analyzed using the Miles & Huberman interactive model (data reduction, data display, conclusion drawing). The results showed that Karangrejo Village's financial recording has used the Siskeudes application systematically since 2012. Tourism revenue from Punthuk Setumbu, Balkondes, and BUMDes contributes dominantly to Village Original Income (PADesa). Recording is carried out independently by each tourism unit with monthly and annual reporting, disclosed transparently to the community and local government without significant obstacles. The study concludes that Karangrejo Tourism Village is feasible as an accounting reporting entity because it has income sources, manages economic resources, conducts financial recording, and prepares accountability reports transparently and accountably.